Motivasi Siswa dalam Pembelajaran Jarak Jauh Pendidikan Jasmani pada Masa Pandemi Covid-19 di SMA Negeri 1 Cariu - Adam Hartono; Nugroho Nugroho; Siswanto Siswanto (Jurnal Ilmiah Wahana Pendidikan, 2022)
The problem in this study is the motivation of students in participating in physical education distance learning during the COVID-19 pandemic at SMA Negeri 1 Cariu. This type of research is a type of quantitative descriptive research and uses a survey method. This data collection technique uses a statement instrument in the form of a questionnaire with data analysis techniques using descriptive statistics with percentages. The population in this study were all students of class XI at SMAN 1 Cariu for the academic year 2021/2022 using the purposive sampling technique. along with respondents totaling 76 students. Based on the results of the research and the information provided so that the minimum value = 63, maximum value = 98, average value = 72, standard deviation = 6 and it is concluded that the level of anxiety of students towards physical education subjects from home is in the "Very High" category 5 respondents with a percentage of 6%, the category "High" 12 respondents with a percentage of 15%, the category "Medium" 34 respondents with a percentage of 44%, the category "Low" 26 respondents with a percentage of 33%, and the category "Very Low" 1 respondent with a percentage of 1%. It can be concluded that students' motivation in distance learning physical education during the COVID-19 pandemic at SMA Negeri 1 Cariu is in a fairly good category.